A statistical analysis of heliospheric plasma sheets, heliospheric current sheets, and sector boundaries observed in situ by STEREO. Issue 11 (3rd November 2014) - Liu, Y. C.‐M.; Huang, J.; Wang, C.; Klecker, B.; Galvin, A. B.; Simunac, K. D. C.; Popecki, M. A.; Kistler, L.; Farrugia, C.; Lee, M. A.; Kucharek, H; Opitz, A.; et al.
Abstract The heliocentric orbits of STEREO A and B with a separation in longitude increasing by about 45° per year provide the unique opportunity to study the evolution of the heliospheric plasma sheet (HPS) on a time scale of up to ~2 days and to investigate the relative locations of HPSs and heliospheric current sheets (HCSs). Previous work usually determined the HCS locations based only on the interplanetary magnetic field. A recent study showed that a HCS can be taken as a global structure only when it matches with a sector boundary (SB). Using magnetic field and suprathermal electron data, it was also shown that the relative location of HCS and SB can be classified into five different types of configurations. However, only for two out of these five configurations, the HCS and SB are located at the same position and only these will therefore be used for our study of the HCS/HPS relative location. We find that out of 37 SBs in our data set, there are 10 suitable HPS/HCS event pairs. We find that an HPS can either straddle or border the related HCS. Comparing the corresponding HPS observations between STEREO A and B, we find that the relative HCS/HPS locations are mostly similar. In addition, the time difference of the HPSs observations between STEREO A and B match well with the predicted time delay for the solar wind coming out of a similar region of the Sun. We therefore conclude that HPSs are stationary structures originating at the Sun.